L10 type iron-nickel ordered alloy and manufacturing method of L10 type iron-nickel ordered alloy

By using sulfur-containing FeNi alloy in the nitriding process, the thermal decomposition of nitride is suppressed, and the problem of low nitriding efficiency in the traditional method is solved, and the effect of reducing production costs and improving ammonia efficiency is achieved.

CN119913395APending Publication Date: 2025-05-02DENSO CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510115726.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-26
Filing Date
2022-09-23
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

In traditional nitriding and denitrification methods, in order to synthesize FeNi super-lattice precursor FeNi, a large amount of ammonia is required, and the nitriding efficiency is low, which increases the production cost of FeNi super-lattice magnetic powder.

Method used

By using a sulfur-containing FeNi alloy in the nitriding process, thermal decomposition of nitride is suppressed and nitriding efficiency is improved. The specific method includes nitriding the sulfur-containing FeNi alloy to obtain a Fe and Ni-containing nitride.

Benefits of technology

The nitriding efficiency is improved, the production cost of FeNi super-lattice magnetic powder is reduced, and the ammonia efficiency is improved without deteriorating magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913395A_ABST
    Figure CN119913395A_ABST
Patent Text Reader

Abstract

The present application relates to an L10-type iron nickel (FeNi) ordered alloy having an L10-type ordered structure and containing sulfur. The L10-type FeNi ordered alloy may have a sulfur content in the range of 0.01 mass% to 10 mass%. A method for manufacturing an L10-type FeNi ordered alloy includes nitriding a FeNi alloy containing sulfur to obtain a nitride containing Fe and Ni.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with application number 202211162901.1 and invention name “L10-type iron-nickel ordered alloy and method for manufacturing L10-type iron-nickel ordered alloy”. Technical Field

[0002] The present disclosure relates to an L10-type iron-nickel (FeNi) ordered alloy having an L10-type ordered structure (hereinafter, also referred to as FeNi superlattice) and a method for producing the L10-type FeNi ordered alloy. Background Art

[0003] FeNi superlattice is expected to be a magnet material and a magnetic device material such as a magnetic recording material having high heat resistance. For example, Japanese Patent No. 6332359 discloses a method for manufacturing a high-quality FeNi superlattice. In this manufacturing method, a high-quality FeNi superlattice is manufactured by a nitriding and denitriding method, wherein a FeNi alloy is nitrided by a nitriding treatment to obtain a nitride, and then nitrogen is desorbed from the nitride by a denitriding treatment. Summary of the invention

[0004] However, in conventional nitriding and denitriding methods, in the nitriding treatment with FeNi alloy as raw material, a large amount of ammonia (NH3) is required to synthesize FeNiN, the precursor of FeNi superlattice, and the fact that the nitriding efficiency is low is one of the factors that increase the production cost of FeNi superlattice magnetic powder.

[0005] The inventors of the present invention have conducted repeated studies to improve the nitriding efficiency and have confirmed that the nitriding efficiency is reduced due to thermal decomposition of nitrides generated in the nitriding process.

[0006] In view of the above points, the object of the present disclosure is to provide an L10-type FeNi ordered alloy and a method for manufacturing the L10-type FeNi ordered alloy, which can reduce production costs by improving nitriding efficiency.

[0007] According to one aspect of the present disclosure, the L10-type FeNi ordered alloy has an L10-type ordered structure and contains sulfur.

[0008] When the L10 type FeNi ordered alloy contains sulfur, that is, when the L10 type FeNi ordered alloy is formed using a FeNi alloy containing sulfur as a raw material, high nitriding efficiency can be obtained.

[0009] According to another aspect of the present disclosure, a method for manufacturing an L10-type FeNi ordered alloy includes nitriding a sulfur-containing FeNi alloy to obtain a nitride containing Fe and Ni.

[0010] In this way, when the sulfur-containing FeNi alloy is nitrided, a high nitriding efficiency can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] The above and other objects, features and advantages of the present disclosure will become more apparent from the following detailed description taken in conjunction with the accompanying drawings. In the drawings:

[0012] Figure 1 is a schematic diagram showing the lattice structure of the L10-type FeNi ordered structure;

[0013] Figure 2 is a schematic diagram showing the lattice structure of FeNiN;

[0014] Figure 3 is a flow chart showing a synthesis process of a FeNi superlattice according to a first embodiment;

[0015] Figure 4 is a flow chart showing a synthesis process of a FeNi superlattice according to a second embodiment;

[0016] Figure 5 is a diagram showing the differences in FeNi superlattice manufacturing conditions, FeNiN formation rate, ammonia efficiency, etc. between each embodiment and comparative example;

[0017] Figure 6 2 is a diagram showing the measurement results of the powder X-ray diffraction (XRD) patterns of Comparative Example 2 and Example 3;

[0018] 7A to 7D 1 is a diagram showing the results of cross-sectional TEM observation and composition image observation using a transmission electron microscope (TEM);

[0019] FIG. 8A to FIG. 8D is a diagram showing the results of cross-sectional TEM observation and composition image observation using TEM;

[0020] Fig. 9 is a diagram showing the differences in FeNi superlattice manufacturing conditions, FeNiN formation rate, ammonia efficiency, etc. between each embodiment and comparative example;

[0021] Fig.10 is a diagram showing the differences in FeNi superlattice manufacturing conditions, FeNiN formation rate, ammonia efficiency, etc. between each embodiment and comparative example;

[0022] Fig.11 is a graph showing the magnetic properties of FeNi superlattice magnetic powders obtained using FeNiN of Comparative Example 2, Example 3, and Example 7; and

[0023] Fig.12It is a diagram showing the X-ray absorption near-edge spectroscopy (XANES) of the FeNi superlattice magnetic powder of Example 3 and Example 4 respectively. Detailed implementation manners

[0024] Hereinafter, embodiments of the present disclosure will be described in detail. However, the embodiments described below are examples for embodying the technical concept of the present disclosure, and the present disclosure is not limited to the following embodiments. In the present disclosure, the term "process" is used not only as an independent process but also as a process included in other processes as long as the intended purpose of the process is achieved, even if it cannot be clearly distinguished from other processes. In addition, the numerical range indicated by using "to" means a range including the values before and after "to" as the minimum value and the maximum value respectively. In the embodiments described below, the same or equivalent parts will be denoted by the same reference numerals.

[0025] <L10-type FeNi ordered alloy>

[0026] The L10-type FeNi ordered alloy of the present embodiment has an L10 ordered structure and contains sulfur. The L10-type ordered alloy mentioned here means that the degree of order is 0.1 or more, and may preferably be 0.5 or more. In addition, the upper limit of the degree of order may be 1 or less. The L10-type FeNi ordered alloy according to the present embodiment is suitable for use as magnetic powder and magnetic materials. Examples of magnetic materials include magnetic materials such as sintered magnets, bonded magnets, and magnetic recording materials. The degree of order S reg represents the degree of order in the FeNi superlattice. The L10-type ordered structure has a structure based on a face-centered cubic lattice and has a lattice structure as Figure 1 shown. In Figure 1 , the uppermost layer in the stacking structure on the (001) plane of the face-centered cubic lattice is defined as site I, and the intermediate layer arranged between the uppermost layer and the lowermost layer is defined as site II. In this case, the occupancy ratio of metal A at site I is defined as x, and the occupancy ratio of metal B at site I is defined as (1 - x). The occupancy ratio of metal A and metal B at site I is expressed as A x B 1-x . Similarly, the occupancy ratio of the metals at site II is defined as x, and the occupancy ratio of metal A at site II is defined as (1 - x). The occupancy ratio of metal A and metal B at site II is expressed as A 1-x B x . Here, x satisfies the relationship of 0.5 ≤ x ≤ 1. In this case, the degree of order S reg is defined as S reg = 2x - 1.

[0027] The degree of order S in the L10-type FeNi ordered alloy shown in the following equation 1 is used: reg The evaluation equation is used to evaluate the order S reg 's evaluation.

[0028] (Equation 1)

[0029]

[0030] Here, in Equation 1, “I sup "I" is the integrated intensity of the diffraction peak (superlattice diffraction peak) peculiar to the L10-type ordered alloy, and is obtained in the X-ray diffraction (XRD) pattern observed by the XRD method. fund " is the integrated intensity of the diffraction peak (basic diffraction peak) that appears in both the FeNi alloy and the L10 type FeNi ordered alloy. "(I sup / I fund ) obs " is the ratio of the integrated intensity of the superlattice diffraction peak to the integrated intensity of the basic diffraction peak in the X-ray diffraction pattern measured in each Example and Comparative Example. In addition, "(I sup / I fund ) cal ” is the ratio of the integrated intensity of the superlattice diffraction peak of the FeNi ordered alloy with an order degree of 1 to the integrated intensity of the fundamental diffraction peak evaluated by the Rietbelt simulation. The order degree S is obtained by calculating the square root of these two ratios as shown in Equation 1. reg As the XRD apparatus used here, a general apparatus such as SmartLab manufactured by Rigaku Co., Ltd. can be used, but the degree of order S can be accurately evaluated by using Fe-kβ rays as X-rays. reg .

[0031] The lower limit of the amount of sulfur (S) in the L10 type FeNi ordered alloy can be, for example, 0.01 mass % or more, preferably 0.03 mass % or more, and more preferably 0.1 mass % or more. The upper limit of the amount of S in the L10 type FeNi ordered alloy can be, for example, 10 mass % or less, preferably 2.0 mass % or less, more preferably 1.5 mass % or less, more preferably 1.0 mass % or less, more preferably 0.75 mass % or less, and particularly preferably 0.53 mass % or less. The S content can be measured by the method described in the following examples.

[0032] The oxidation number of sulfur (S) in L10-type FeNi ordered alloys can include S 2- or S 6+ or S 2- and S 6+The oxidation number of sulfur can be determined by XAFS measurement (i.e., partial fluorescence yield measurement) described later. The absorption peak appearing at 2482.0±2 eV in the XAFS measurement can be considered to be due to S 6+ The peak at 2471.5±2eV can be considered to be due to S 2- Based on the presence of these absorption peaks, it can be determined that S 2- and S 6+ In addition, the oxidation number of sulfur contained in the FeNi superlattice can be S 2- and S 6+ Any value other than may be used as long as the effect of improving ammonia efficiency can be obtained.

[0033] The L10-type FeNi ordered alloy may be composed of particles 100 having an L10-type ordered structure, as shown in Figures 7 and 8 described later. In the case where the L10-type FeNi ordered alloy is composed of particles 100 having an L10-type ordered structure, S may be present throughout the particles, may be segregated inside the particles, or may be segregated on the surface of the particles. The state of S may be determined by the method described in the following examples.

[0034] In the case where the L10 type FeNi ordered alloy is composed of particles with an L10 type ordered structure, the lower limit of the average particle size can be, for example, 10 nm or more, preferably 50 nm or more, more preferably 100 nm or more. In addition, the upper limit of the average particle size can be, for example, 5000 nm or less, preferably 1000 nm or less, more preferably 500 nm or less. The average particle size can be measured by a scanning electron microscope (SEM) image.

[0035] L10 type FeNi ordered alloy can be composed of secondary particles in which primary particles are aggregated, and in this case, the lower limit of the average particle size of the primary particles can be, for example, 10nm or more, preferably 30nm, more preferably 50nm or more. In addition, the upper limit of the average particle size of the primary particles can be, for example, 1000nm or less, preferably 500nm or less. The average particle size of the primary particles can be calculated by analyzing the XRD pattern with the Williamson-Hall method.

[0036] The ratio of the molar number of Fe to the total molar number of Fe and Ni in the L10 type FeNi ordered alloy may be 0.4 to 0.6, preferably 0.45 to 0.55, more preferably 0.48 to 0.52. The molar number of Fe and Ni can be measured by inductively coupled plasma (ICP) emission spectrometry or energy dispersive X-ray spectroscopy (EDS) using an electron microscope, etc.

[0037] <Method for manufacturing L10-type FeNi ordered alloy>

[0038] The method for manufacturing an L10-type FeNi ordered alloy according to the present embodiment includes subjecting a FeNi alloy containing sulfur (S) to a nitriding treatment to obtain a nitride containing Fe and Ni. According to the present embodiment, since the FeNi alloy used in the nitriding step contains S, thermal decomposition of the FeNi nitride formed in the nitriding step can be suppressed, which is considered to improve the nitriding efficiency. The L10-type FeNi ordered alloy manufactured according to the present embodiment is suitable for use as magnetic powder and magnetic materials. Examples of magnetic materials include magnetic materials such as sintered magnets, bonded magnets, and magnetic recording materials.

[0039] <Nitriding step>

[0040] In the nitriding step, a S-containing FeNi alloy (hereinafter also referred to as FeNi-S) is nitrided to obtain a nitride containing Fe and Ni (hereinafter referred to as FeNi nitride). The nitriding treatment is not particularly limited as long as it can obtain FeNi nitride from FeNi-S, but examples of the nitriding treatment include gas nitriding with ammonia gas or nitrogen gas, plasma nitriding, and nitriding with metal amides. In particular, the nitriding treatment is carried out by heat-treating the pre-prepared FeNi-S under an ammonia gas stream. The flow rate of ammonia gas in the nitriding treatment can be 0.1 to 10 liters per minute relative to 1 g of FeNi-S, preferably 0.5 to 5 liters per minute. The heat treatment temperature can be, for example, 300 to 500 °C, preferably 310 to 475 °C, more preferably 330 to 450 °C. The heat treatment time can be, for example, 5 to 50 hours, preferably 10 to 20 hours. The FeNi nitride obtained in the nitriding step can be a S-containing FeNi nitride (hereinafter also referred to as FeNi nitride-S).

[0041] The S-containing FeNi alloy used in the nitriding step may have a disordered structure. The disordered structure mentioned here can be a structure in which the arrangement of atoms is irregular and there is no degree of order, or a structure in which no peak of the L10-type ordered structure is observed when measured by X-ray diffraction.

[0042] The FeNi-S used in the nitriding process can be manufactured as needed by adding a compound containing a predetermined amount of sulfur element (hereinafter also referred to as a sulfur compound) to the FeNi alloy manufactured by a known method. FeNi-S can also be manufactured by mixing the FeNi alloy and the sulfur compound and then heat treating it, or by reacting the FeNi alloy and the sulfur compound. FeNi-S can also be manufactured by partially sulfiding the FeNi alloy with hydrogen sulfide gas or the like. The sulfur compound should contain sulfur element, and examples of the sulfur compound include sulfur, organic sulfur compounds, metal sulfides (such as iron sulfide and nickel sulfide) and sulfates (such as ammonium sulfate, iron sulfate and nickel sulfate).

[0043] The FeNi-S used in the nitriding process can be synthesized during the nitriding process. In particular, for example, the FeNi nitride is formed into a layer by heat treating the FeNi alloy under a mixed gas flow of ammonia and hydrogen sulfide, so that the synthesis of the FeNi nitride-S and nitriding (sulphonitriding) are carried out in parallel.

[0044] The ratio of the molar number of Fe to the total molar number of Fe and Ni in FeNi-S used in the nitriding step may be 0.4 to 0.6, preferably 0.45 to 0.55, and more preferably 0.48 to 0.52.

[0045] The sulfur (S) content in the FeNi-S used in the nitriding process can be, for example, 0.01 mass % to 10 mass %, preferably 0.02 mass % to 2.0 mass %, more preferably 0.02 mass % to 1.5 mass %, more preferably 0.03 mass % to 1.0 mass %, and particularly preferably 0.05 mass % to 0.7 mass %. When the S content in the FeNi-S used in the nitriding process is within the above range, there is a tendency to promote nitriding while suppressing the deterioration of the magnetic properties of the finally obtained FeNi ordered alloy. The sulfur content can be measured by the method described in the following examples.

[0046] Examples of FeNi nitrides obtained in the nitriding process include FeNiN, Fe2Ni2N, etc. In order to obtain an L10 type FeNi ordered alloy, it is preferred that the proportion of FeNiN is larger. FeNiN has the following characteristics: Figure 2 The crystal structure shown in and can be identified by the XRD diffraction pattern. The proportion of FeNi nitride contained after the nitriding process can be 90 mass % or more of the entire product. The proportion of FeNiN in the FeNi nitride can be 50 mass % or more, preferably 80 mass % or more. The nitride ratio and FeNiN ratio after the nitriding process can be calculated by analyzing the XRD diffraction pattern by the reference intensity ratio (RIR) method.

[0047] In the FeNi nitride obtained in the nitriding process, the ratio of the molar number of Fe to the total molar number of Fe and Ni may be 0.4 to 0.6, preferably 0.45 to 0.55, and more preferably 0.48 to 0.52. The molar number of Fe and Ni can be measured by inductively coupled plasma (ICP) emission spectrometry or energy dispersive X-ray spectroscopy (EDS) using an electron microscope, etc.

[0048] The FeNi nitride obtained in the nitriding process may contain sulfur (S). In the case where the FeNi nitride contains S, the lower limit of the S content may be, for example, 0.01 mass % or more, preferably 0.03 mass % or more, more preferably 0.05 mass % or more. The upper limit of the S content in the L10 type FeNi ordered alloy may be, for example, 10 mass % or less, preferably 2.0 mass % or less, more preferably 1.5 mass % or less, more preferably 1.0 mass % or less, particularly preferably 0.7 mass % or less. The S content may be determined by the method described in the following examples.

[0049] In the case where the FeNi nitride obtained in the nitriding process contains S, the FeNi nitride may be composed of particles. In the case where the FeNi nitride is composed of particles, S may be present in the entire particle, or may be segregated inside the particle. In addition, S may be segregated on the surface of the particle. The state of S may be measured by the method described in the following examples.

[0050] In the case where the FeNi nitride obtained in the nitriding process is composed of particles, the lower limit of the average particle size can be, for example, 10 nm or more, preferably 50 nm or more, more preferably 100 nm or more. In addition, the upper limit of the average particle size can be, for example, 5000 nm or less, preferably 1000 nm or less, more preferably 500 nm or less. The average particle size can be measured by a scanning electron microscope (SEM) image.

[0051] The FeNi nitride obtained in the nitriding process can be composed of secondary particles in which the primary particles are aggregated, and in this case, the lower limit of the average particle size of the primary particles can be, for example, 10 nm or more, preferably 30 nm or more, more preferably 50 nm or more. In addition, the upper limit of the average particle size can be, for example, 1000 nm or less, preferably 500 nm or less. The average particle size of the primary particles can be calculated by analyzing the XRD pattern using the Williamson-Hall method.

[0052] In the nitriding process, FeNi-S is nitrided. Therefore, as shown in the embodiments described later, a high nitriding efficiency can be obtained. The nitriding efficiency in the nitriding process can be greater than 4.7×10-5 , preferably greater than 10×10 -5 , more preferably greater than 20×10 -5 . The term "nitriding efficiency" used in the present disclosure refers to a number obtained by dividing the amount of FeNiN formed by the nitriding treatment (g) by the nitrogen raw material consumed in the nitriding treatment (g). The nitriding efficiency in the case where ammonia is used as a nitrogen source (hereinafter referred to as ammonia efficiency) refers to a value obtained by dividing the amount of FeNiN formed (g) by the amount of ammonia consumed (g), which is the amount of ammonia required to synthesize FeNiN. A higher ammonia efficiency value means that FeNiN can be synthesized with a smaller amount of ammonia.

[0053] In the nitriding process, an L10-type FeNi ordered alloy containing S can be used as the FeNi alloy. In addition to the L10-type FeNi ordered alloy containing S described in the present embodiment, the L10-type FeNi ordered alloy containing S can also be obtained by adding a predetermined amount of sulfur compound as needed to the L10-type FeNi ordered alloy manufactured by a known method. The L10-type FeNi ordered alloy containing S can also be manufactured by mixing the L10-type FeNi ordered alloy with a sulfur compound and then heat treating it, or by reacting the L10-type FeNi ordered alloy with a sulfur compound. The L10-type FeNi ordered alloy containing S can also be manufactured by partially sulfiding the L10-type FeNi ordered alloy with hydrogen sulfide gas, etc. The sulfur compound is as described above. In the case where FeNi-S having an L10-type ordered structure is used, an improvement in order can be expected.

[0054] [Denitrification process]

[0055] In the denitrification process, the FeNi nitride obtained in the above-mentioned nitriding process is denitrified to obtain an L10 type FeNi ordered alloy. In particular, after the FeNi nitride obtained in the nitriding process is crushed, the denitrification treatment can be carried out by heat treating it in a hydrogen atmosphere. The flow rate of hydrogen in the denitrification treatment can be 0.01 to 10 liters / minute relative to 1g of FeNi nitride-S, preferably 0.1 to 5 liters / minute. The heat treatment temperature can be, for example, 100 to 400°C, preferably 200 to 350°C. The heat treatment time can be, for example, 1 to 24 hours, preferably 2 to 10 hours. The L10 type FeNi ordered alloy obtained in the denitrification process can be an L10 type FeNi ordered alloy containing S.

[0056] An example of a method for producing a FeNi alloy containing S used in a nitriding process will be described below.

[0057] (First embodiment)

[0058] like Figure 3As shown in , the production method according to the first embodiment includes a reduction step of reducing FeNi oxide containing S (hereinafter, also referred to as FeNi oxide-S) to obtain FeNi-S.

[0059] The reduction method in the reduction process is not particularly limited, but for example, FeNi-S can be obtained by heat treating FeNi oxide containing S in a reducing gas atmosphere. The flow rate of the reducing gas can be 1 liter / minute relative to 8.5g of FeNi oxide-S, preferably 0.5 to 10.0 liters / minute. The heat treatment temperature can be, for example, 300 to 700°C, preferably 450 to 700°C. The heat treatment time can be, for example, 1 to 10 hours, preferably 1.5 hours. Examples of reducing gases include hydrogen and carbon monoxide, and from the viewpoint of reducing characteristics, hydrogen is preferred.

[0060] The ratio of the molar number of Fe in FeNi oxide-S to the total molar number of Fe and Ni may be 0.4 to 0.6, preferably 0.45 to 0.55, and more preferably 0.48 to 0.52.

[0061] The FeNi oxide-S used in the reduction step may contain Fe oxide, Ni oxide, or an oxide containing Fe and Ni. In addition, Fe oxide, Ni oxide, and an oxide containing Fe and Ni may each contain S. The Fe and Ni oxide used here refers to an oxide particle containing Fe element and Ni element.

[0062] The FeNi oxide-S used in the reduction step can be produced by adding a predetermined amount of a sulfur compound to the FeNi oxide produced by the present embodiment or a known method as needed. The FeNi oxide-S can also be produced by mixing the FeNi oxide and the sulfur compound and then heat treating it, or by reacting the FeNi oxide and the sulfur compound. The FeNi oxide-S can also be produced by partially sulfiding the FeNi oxide with hydrogen sulfide gas or the like. The sulfur compound is as described above.

[0063] The FeNi oxide-S used in the reduction process can be synthesized during the reduction process. Specifically, for example, the FeNi oxide is heat-treated under a mixed gas flow of hydrogen and hydrogen sulfide, so that the synthesis and reduction of the FeNi oxide-S are carried out in parallel.

[0064] Fe oxide is not particularly limited. Examples of Fe oxide include FeO, Fe2O3, Fe3O4, and oxides obtained by oxidizing iron metal, iron hydroxide, iron carbonate, iron chloride, iron iodide, iron bromide, iron sulfate, iron nitrate, iron phosphate, and iron oxalate. Among these substances, iron sulfate is preferred because it serves as a sulfur source for Fe oxide containing S. Fe oxide containing S can be manufactured by the preparation method of the above-mentioned FeNi oxide-S.

[0065] Ni oxide is not particularly limited. Examples of Ni oxide include NiO, and oxides obtained by oxidizing nickel metal, nickel hydroxide, nickel carbonate, nickel chloride, nickel iodide, nickel bromide, nickel sulfate, nickel nitrate, nickel phosphate and nickel oxalate. Among these substances, nickel sulfate is preferred because it serves as a sulfur source for Ni oxide containing S. Ni oxide containing S can be manufactured by the above-mentioned FeNi oxide-S manufacturing method.

[0066] The Fe and Ni-containing oxide can be prepared by mixing a solution containing Fe and Ni with a precipitant to obtain a precipitate containing Fe and Ni (precipitation process), and heat-treating the precipitate to obtain an Fe and Ni-containing oxide (oxidation process). According to this method, the average particle size and particle size distribution of the obtained Fe and Ni-containing oxide are easily controlled, and the distribution of the Fe element and the Ni element in the Fe and Ni-containing oxide tends to be uniform.

[0067] [Precipitation process]

[0068] In the precipitation process, a Fe raw material and a Ni raw material are dissolved in a strongly acidic solution to prepare a solution containing Fe and Ni.

[0069] Fe raw material and Ni raw material are not limited as long as they can be dissolved in acidic solution. Examples of Fe raw materials include iron metal, iron oxide, iron hydroxide, iron carbonate, iron chloride, iron iodide, iron sulfate, iron nitrate, iron phosphate, iron oxalate, etc. It is preferred to use iron metal, iron carbonate, iron sulfate or iron chloride, and more preferably use iron sulfate because it serves as a sulfur source for the precipitate containing S. Examples of Ni raw materials include nickel metal, nickel oxide, nickel hydroxide, nickel carbonate, nickel chloride, nickel iodide, nickel sulfate, nickel nitrate, nickel phosphate and nickel oxalate. It is preferred to use nickel metal, nickel carbonate, nickel sulfate or nickel chloride, and more preferably use nickel sulfate because it serves as a sulfur source for the precipitate containing S. Examples of acidic solutions include sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, etc. Among these substances, sulfuric acid is preferred because it serves as a sulfur source for the precipitate containing S, Fe and Ni. The concentration of the solution containing Fe and Ni can be appropriately adjusted within the range in which the Fe raw material and the Ni raw material are substantially dissolved in the acidic solution.

[0070] In the solution containing Fe and Ni, the ratio of the mole number of Fe to the total mole number of Fe and Ni may be 0.4 to 0.6, preferably 0.45 to 0.55, and more preferably 0.48 to 0.52.

[0071] The precipitate containing Fe and Ni is obtained by reacting a solution containing Fe and Ni with a precipitant. In the reaction of the solution containing Fe and Ni with the precipitant, the precipitant can be added to the solution containing Fe and Ni, or the solution containing Fe and Ni can be added to the precipitant. The solution containing Fe and Ni mentioned here can be a solution containing Fe and Ni when reacting with the precipitant. The raw materials containing Fe and Ni can be prepared into separate solutions, and these solutions can be added to react with the precipitant. Even in the case where they are prepared into separate solutions, each raw material is substantially dissolved in the acidic solution. Adjust as appropriate. The precipitant is not limited, as long as it reacts with the solution containing Fe and Ni to obtain a precipitate. Examples of precipitants include: oxalic acid and alkaline solutions, such as sodium hydroxide aqueous solution, sodium bicarbonate aqueous solution, potassium hydroxide aqueous solution and lithium hydroxide aqueous solution. The precipitate can also be obtained by blowing carbon dioxide into a solution containing Fe and Ni. Examples of precipitates include oxalates, carbonates, hydroxides, etc.

[0072] The precipitation process may include a process of separating and washing the precipitate. As a method of separating the precipitate, for example, a filtration method or a decantation method may be used after adding a solution (preferably water) to the obtained precipitate and mixing them. In addition, washing may be performed by repeating the same process for the precipitate that has been separated.

[0073] After separating the precipitate, in order to prevent the precipitate from being redissolved in the residual solvent in the heat treatment of the subsequent oxidation process and agglomerating the precipitate when the solvent evaporates, the solvent is preferably removed from the precipitate. As a specific example of the method of removing the solvent, for example, in the case where water is used as the solvent, the precipitate can be dried in an oven at a temperature ranging from 70 to 200° C. for 5 to 12 hours. After drying, if necessary, the particles can be crushed or pulverized to adjust the particle size.

[0074] The precipitate containing S, Fe and Ni can be obtained by adding a predetermined amount of sulfur compound as needed during the reaction between the solution containing Fe and Ni and the precipitant or after the reaction, and can be obtained by adding the sulfur compound in the separation and washing process. The precipitate containing S, Fe and Ni can also be prepared by adding a predetermined amount of sulfur compound to the obtained precipitate, or by reacting the precipitate with the sulfur compound as needed. The reaction between the precipitate and the sulfur compound can be carried out, for example, by mixing the precipitate and the sulfur compound and then heat-treating the mixture. The precipitate containing S, Fe and Ni can also be manufactured by sulfiding a part of the precipitate with hydrogen sulfide gas, etc. The sulfur compound is as described above.

[0075] [Oxidation process]

[0076] The oxidation process is a process for obtaining an oxide containing Fe and Ni by heat-treating the precipitate containing Fe and Ni obtained in the precipitation process. The oxidation process can convert the precipitate into an oxide, for example, by heat treatment. When the precipitate is heat-treated, the heat treatment must be carried out in the presence of oxygen and can be carried out, for example, in an air atmosphere. In addition, since the heat treatment must be carried out in the presence of oxygen, it is preferred that the non-metallic part of the precipitate contains oxygen atoms. When a precipitate containing S, Fe and Ni is used in the oxidation process, FeNi oxide-S can be obtained. If necessary, the obtained FeNi oxide-S can be crushed or pulverized to adjust the particle size.

[0077] The heat treatment temperature in the oxidation step (hereinafter referred to as oxidation temperature) is not particularly limited, but may be, for example, 200 to 800° C., preferably 350 to 450° C. The heat treatment time may be, for example, 4 to 24 hours, preferably 8 hours.

[0078] The obtained oxide is oxide particles in which Fe and Ni are microscopically thoroughly mixed, and the shape, particle size distribution, etc. of the precipitate are reflected.

[0079] The precipitate containing S, Fe and Ni used in the oxidation step can be synthesized during the oxidation step. Specifically, for example, the precipitate containing Fe and Ni is heat-treated under a mixed gas flow of air and hydrogen sulfide, so that the synthesis and oxidation of the precipitate containing S, Fe and Ni proceed in parallel.

[0080] (Second embodiment)

[0081] The second embodiment is described below. This embodiment differs from the first embodiment in the method for manufacturing FeNiN, and the other parts are similar to the first embodiment. Therefore, only the parts different from the first embodiment will be described below. Figure 4 The flowchart shown in describes the method for manufacturing the FeNi superlattice according to the present embodiment.

[0082] First, if Figure 4 As shown in , an FeNi alloy to which S is added is manufactured. In particular, first, FeNi powder is prepared. It is preferred to prepare FeNi powder having a composition ratio of Fe:Ni=50:50. The composition ratio of Fe:Ni may be approximately 50:50. For example, it is sufficient for the proportion of Fe to be 50±3% and the proportion of Ni to be the remaining {100-(50±3)}%. As such FeNi powder, for example, FeNi nanoparticles synthesized by a thermal plasma method manufactured by Nisshin Engineering Co., Ltd., FeNi powder synthesized by a gas atomization method manufactured by Epson Atmix, etc. may be used.

[0083] Next, the FeNi powder is reacted in a mixed gas of H2S gas and nitrogen (N2) gas. As a result, FeNi-S is obtained, which is a FeNi alloy to which S is added. For example, 3% H2S gas + 97% N2 gas is used as a mixed gas, and heat treatment is performed at 200 to 500°C for 2 to 24 hours to obtain FeNi-S.

[0084] Thereafter, nitriding treatment is performed in the same manner as in the first embodiment to synthesize FeNiN-S, and then further denitrification treatment is performed to obtain FeNi superlattice. The FeNi superlattice obtained as described above also contains S. In this case as well, high ammonia efficiency can be obtained as shown in the examples described later.

[0085] Hereinafter, examples in which FeNi—S was produced by various methods including the production method of the above-described embodiment and then subjected to nitriding and denitriding treatments were compared with a comparative example using FeNi containing no sulfur.

[0086] Figure 5Graph showing how the manufacturing conditions of the FeNi superlattice, the formation rate of FeNiN, the ammonia efficiency, etc., vary in each embodiment and the comparative (COMP) example. Figure 5 In the S doping method in the embodiment, (1) represents the manufacturing method of the first embodiment, and (2) represents the manufacturing method of the second embodiment, and the details of Examples 1 to 5 are described later. Example 6 shows a case where FeNi-S is synthesized by reacting FeNi alloy particles manufactured by the gas atomization method of the second embodiment with ammonium sulfate. Example 7 shows a case where FeNi-S is synthesized by reacting ammonium sulfate with FeNi alloy particles manufactured by the thermal plasma method in the second embodiment. Comparative Examples 1 and 2 show a case where FeNi manufactured by the thermal plasma method is subjected to nitriding and denitrification treatment without reacting with ammonium sulfate.

[0087] Notice, Figure 5 The sulfur content (mass %) shown in (i.e., the mass ratio of S to the total mass of Fe, Ni and S) is evaluated by using a commonly used element mass analysis method. For example, the sulfur content can be determined by inductively coupled plasma (ICP) emission spectrometry or energy dispersive X-ray spectrometry (EDS) using an electron microscope. The sulfur content (mass %) before and after nitriding and denitriding treatment is substantially the same. The FeNiN formation rate is the ratio of the amount of FeNiN formed after nitriding treatment to the amount of FeNi alloy before nitriding treatment, and is calculated by the reference intensity ratio (RIR) method by measuring the powder XRD pattern. More specifically, the FeNiN formation rate is: the amount of FeNiN actually obtained relative to the ratio of the ideal FeNiN formation amount when it is considered that the total amount of FeNi alloy contained in the raw material before nitriding treatment is obtained as FeNiN by nitriding treatment. The RIR values ​​of FeNiN, Fe2Ni2N and FeNi alloy stored in the database of the analysis software (PDXL2) attached to the XRD device (SmartLab manufactured by Rigaku Corporation) are used to analyze the formation rate by the RIR method. In addition, the efficiency improvement rate indicates the ratio of the ammonia efficiency in each of Comparative Example 1 and Examples 1 to 7 in the case where Comparative Example 2 is used as a reference (REF).

[0088] Hereinafter, Examples 1 to 7, 9, 10, 12 and 13 are described in detail. Unless otherwise specified, "%" is based on mass.

[0089] (Example 1)

[0090] [Precipitation process]

[0091] First, 0.34 liters of 5 mass % iron sulfate aqueous solution and 0.2 liters of 9 mass % nickel sulfate aqueous solution were added to 3 liters of 10 mass % oxalic acid aqueous solution being stirred so that the molar ratio of iron to nickel became 50:50. Thus, an oxalate slurry containing Fe, Ni and S was obtained. After the resulting slurry was washed with pure water by decantation, the oxalate containing Fe and Ni was separated into solid and liquid. The separated oxalate containing Fe and Ni was dried in an oven at 100 ° C for 10 hours. The S contained in the oxalate is believed to be due to the sulfate ions of the iron sulfate or nickel sulfate as the raw material.

[0092] [Oxidation process]

[0093] Subsequently, 50 g of the obtained oxalate containing Fe, Ni and S was heat-treated in air at 400° C. for 8 hours. After cooling, an oxide containing Fe, Ni and S was obtained.

[0094] [Reduction process]

[0095] Subsequently, 8.5 g of the oxide containing Fe, Ni and S was heat treated at 450° C. for 1.5 hours in a hydrogen atmosphere (hydrogen flow rate 1 liter / minute). After cooling, a FeNi alloy containing S was obtained. The sulfur content in the alloy was 0.03% by mass. The sulfur content was determined by dissolving the FeNi alloy containing S in hydrochloric acid and measuring the mass ratio of S to the total mass of Fe, Ni and S using an instrument called Optima 8300 by ICP-AES method.

[0096] [Nitriding process]

[0097] Subsequently, 0.4 g of FeNi alloy containing S was heat treated at 335° C. for 40 hours in an ammonia atmosphere (ammonia flow rate: 1 liter / minute) to obtain FeNiN. The formation rate of FeNiN was 95%. The FeNiN formation rate was calculated by using Fe kβ rays (wavelength: ) was measured by X-ray diffraction (instrument name: Smartlab, tube current: 200mA, tube voltage: 45kV) and is defined as the ratio of the integrated intensity of the FeNiN peak (40°) to the sum of the integrated intensity of the FeNiN peak and the integrated intensity of the Fe2Ni2N peak (41.5°). In addition to the mass of the FeNi alloy as a raw material and the mass of the obtained FeNi nitride, the FeNiN formation rate was also calculated by measuring the powder XRD pattern using the reference intensity ratio (RIR) method.

[0098] [Denitrification process]

[0099] The obtained FeNiN was heat treated at 250°C for 20 hours in a hydrogen atmosphere (hydrogen flow rate: 1 liter / minute) to obtain an L10 type FeNi ordered alloy. It was confirmed that the sulfur content in the L10 type ordered alloy was 0.03% by mass, which was almost the same as the sulfur content in the S-containing FeNi alloy obtained in the reduction process. The sulfur content was determined by the ICP-AES method after dissolving the obtained FeNi alloy in hydrochloric acid, and was defined as the mass ratio of S to the total mass of Fe, Ni and S.

[0100] (Example 2)

[0101] The same steps as in Example 1 were carried out except that the heat treatment temperature in the nitriding step was changed to 415°C.

[0102] (Example 3)

[0103] The same procedure as in Example 2 was performed except that ammonium sulfate was added and the oxalate containing Fe, Ni and S obtained in Example 1 was heat treated. The amount of ammonium sulfate added was 0.02% by mass relative to the oxalate. As a result, the sulfur content in the alloy particles was 0.05% by mass.

[0104] (Example 4)

[0105] The same procedure as in Example 2 was performed except that ammonium sulfate was added and the oxalate containing Fe, Ni and S obtained in Example 1 was heat treated. The amount of ammonium sulfate added was 0.11% by mass relative to the oxalate. As a result, the sulfur content in the alloy particles was 0.14% by mass.

[0106] (Example 5)

[0107] The same procedure as in Example 2 was performed except that ammonium sulfate was added and the oxalate containing Fe, Ni and S obtained in Example 1 was heat treated. The amount of ammonium sulfate added was 0.45 mass % relative to the oxalate. As a result, the sulfur content in the alloy particles was 0.48 mass %.

[0108] In each of Comparative Examples 1 and 2, since the FeNi superlattice is manufactured by a conventional manufacturing method in which sulfur is not added to FeNi, the sulfur doping method (S doping method) and the sulfur content (mass %) are indicated by "-", which means "none". In the case where the amount of NH3 is 5 liters / minute and nitriding is performed at 300°C for 40 hours as in Comparative Example 2, the formation rate of FeNiN is 99% (which is almost 100%), so the ammonia efficiency at this time is 4.7 (×10 -5), which was used as a reference. On the other hand, when the amount of NH3 was 1 liter / minute as in Comparative Example 1 (which was less than that in Comparative Example 2), the formation rate of FeNiN was only 15%. The ammonia efficiency was only 3.6 (×10 -5 ), and the efficiency improvement rate is 0.76, which is significantly lower than the efficiency improvement rate of Comparative Example 2 serving as a reference.

[0109] It can be seen from this that in the case where FeNi without sulfur addition is subjected to nitriding and denitrification treatment, the amount of NH3 cannot be reduced; unless the amount of NH3 is about 5 liters / minute, the FeNiN formation rate cannot be increased and the ammonia efficiency decreases.

[0110] The temperature during the nitriding treatment is set to 300°C. In the case of FeNi to which sulfur is not added, when the temperature exceeds 300°C, the FeNiN formation rate is unstable, and the ammonia efficiency is similarly reduced. The nitriding treatment time is set to 40 hours. If the time is shorter than 40 hours, the FeNiN formation rate is unstable, and the ammonia efficiency is similarly reduced. The sample amount is set to 400 mg. If the amount of FeNi to be nitrided once is increased, the FeNiN formation rate is unstable, and the ammonia efficiency is similarly reduced. Therefore, as described above, if the amount of NH3 is reduced, the nitriding treatment time is shortened, or the amount of FeNi to be nitrided once is increased, the ammonia efficiency is reduced, and pure FeNiN cannot be obtained.

[0111] On the other hand, in each of Examples 1 to 7, FeNi to which sulfur was added was subjected to nitriding and denitrification treatments, and in all cases of Examples 1 to 7, ammonia efficiency higher than that of the reference was obtained.

[0112] In Example 1, sulfur was as little as 0.03 (mass %), but even when the amount of NH3 was reduced to 1 liter / min under nitriding conditions at 335°C for 40 hours, the FeNiN formation rate was as high as 95%, and the ammonia efficiency was 22.9 (×10 -5 ). The efficiency improvement rate is also a high value of 4.8.

[0113] In Example 2, at the same sulfur content as in Example 1, only the nitriding temperature was increased to 415°C. Although the FeNiN formation rate dropped to 43%, the ammonia efficiency was 10.4 (×10 -5 ), which is higher than the reference. The efficiency improvement rate is also a high value of 2.2.

[0114] In Example 3, the sulfur content was set to 0.05 (mass%) (which was higher than that in Example 1), the FeNiN formation rate was as high as 97%, and the ammonia efficiency was 23.6 (×10 -5). The efficiency improvement rate is also a high value of 4.9. As described later, it has been confirmed that the FeNiN formation rate can be improved by changing the temperature of the nitriding treatment according to the sulfur content. In Example 3, the nitriding temperature is set to 415°C in order to improve the FeNiN formation rate. Therefore, the FeNiN formation rate can be a particularly high value, and a higher ammonia efficiency is obtained.

[0115] In Example 4, the sulfur content was increased to 0.14 (mass %) (which is higher than that in Example 3), and the nitriding conditions were the same as those in Example 3. The FeNiN formation rate was maintained at a high value of 90%, and the ammonia efficiency was maintained at 21.8 (×10 -5 ). The efficiency improvement rate was also a high value of 4.6. In Examples 5 to 7, the sulfur content was increased to more than that in Example 4, and the same nitriding conditions as in Examples 3 and 4 were used. In Example 5, the sulfur content was set to 0.48 (mass %), the FeNiN formation rate was 94%, and the ammonia efficiency was 22.8 (×10 -5 ), and the efficiency improvement rate was 4.8, which are both high values. In Example 6, the sulfur content was set to 1.05 (mass%), the FeNiN formation rate was 92%, and the ammonia efficiency was 22.1 (×10 -5 ), and the efficiency improvement rate was 4.7, which are both high values. In Example 7, the sulfur content was set to 2.26 (mass%), the FeNiN formation rate was 88%, and the ammonia efficiency was 21.2 (×10 -5 ), and the efficiency improvement rate is 4.5, which are both high values.

[0116] For reference, Figure 6 The XRD pattern measurement results of Comparative Example 2 and Example 3 are shown. Figure 6 The circles shown in are XRD diffraction peaks attributable to FeNiN. It can be seen that in both Comparative Example 2 and Example 3, high-purity FeNiN is obtained.

[0117] As can be seen from these Examples 1 to 7, in the case where the FeNi superlattice is manufactured by adding sulfur to FeNi and then performing nitriding and denitriding treatments, the FeNiN formation rate can be increased and the ammonia efficiency can be increased compared to the conventional manufacturing method in which sulfur is not added. In particular, by setting the sulfur content to 0.03 (mass %) or more, the ammonia efficiency can be increased to 2 times or more compared to the conventional manufacturing method. Therefore, in the FeNi superlattice of the present embodiment, by improving the ammonia efficiency, at least one of reducing the amount of NH3, shortening the nitriding time, and increasing the amount of material to be nitrided once can be implemented, which reduces the cost.

[0118] In addition, as in Examples 1 to 5, cross-sectional TEM observation and composition image observation using TEM were performed on the FeNi superlattice produced by the production method of the first embodiment, and the results shown in 7A to 7D were obtained. Fig. 7A The results of cross-sectional TEM observation are shown. Figure 7B shows the S composition image, Figure 7C is the Fe component image, and Fig.7D A Ni composition image is shown.

[0119] In which the FeNi superlattice particles 100 Fig. 7A In the case of the distribution shown in , FeNi exists uniformly, such as Figure 7C and Fig.7D As shown in the composition image of Fe and Ni shown in , the FeNi superlattice is formed in a good state. Then, as Figure 7B As shown in , it can be seen that S exists in a state of being distributed throughout, which corresponds to the distribution of the particle 100 of the FeNi superlattice. The fact that S exists in the entire particle 100 of the FeNi superlattice means that S exists in the entire FeNi alloy or FeNiN particle 100 even in the manufacturing process of the FeNi superlattice. In this way, it can be seen that in the case where S exists in the entire particle 100 of the superlattice (in other words, in the case where S exists in the entire particle 100 of the FeNi alloy or FeNiN in the manufacturing process of the FeNi superlattice), high ammonia efficiency can be obtained.

[0120] like Fig. 7A , Figure 7C and Fig.7D As shown in, in each of Examples 1 to 5, the particle size of the FeNi superlattice is about 100 nm, but the particle size can be appropriately changed according to the purpose of applying the FeNi superlattice, and can be changed, for example, in the range of 100 nm to several μm. According to the experiment, the particle size of the FeNi superlattice varies according to the sintering temperature for obtaining the FeNi oxide and the reduction temperature for obtaining the FeNi alloy, and has a tendency to increase the particle size as the temperature increases. Since the change in particle size affects the magnetic properties and environmental resistance, the sintering temperature and the reduction temperature should be set according to the application purpose of the FeNi superlattice, so that the desired magnetic properties and environmental resistance can be obtained.

[0121] On the other hand, as in Examples 6 and 7, the FeNi superlattice produced by the production method of the second embodiment was also subjected to cross-sectional TEM observation and composition image observation. Then, the results with large particle size were extracted and placed in FIG. 8A to FIG. 8D Shown in. Fig. 8A The results of cross-sectional TEM observation are shown. Figure 8B shows the S composition image, Figure 8C The Fe composition image is shown, and Fig.8D A Ni composition image is shown.

[0122] Even in the Fig. 8A In the case of the FeNi superlattice having a large particle size, as shown in FIG, FeNi is uniformly present in the particle 100. Figure 8C and Fig.8D As shown in the composition image shown in , the FeNi superlattice is formed in a good state. Then, as Figure 8B As shown in , it can be seen that S is segregated and present on the surface of the particle 100 of the FeNi super lattice. The fact that S is segregated on the surface of the particle 100 of the FeNi super lattice means that S is segregated on the surface of the FeNi alloy or FeNiN particle even in the manufacturing process of the FeNi super lattice. Therefore, in the case where S is segregated on the surface of the particle 100 of the FeNi super lattice (in other words, S is segregated on the particle surface of the FeNi alloy or FeNiN even in the manufacturing process of the FeNi super lattice), high ammonia efficiency can be obtained.

[0123] Next, by changing the temperature during the nitriding treatment while maintaining the sulfur content, the FeNiN formation rate, ammonia efficiency, and efficiency improvement rate were examined. Specifically, the experiment was conducted by changing the temperature of the nitriding treatment in the case where the sulfur content was set to 0.14 (mass %) as in the above-mentioned Example 4. In addition, as a comparative example, a similar experiment was conducted on a conventional manufacturing method. Fig. 9 is a graph showing the results. Fig. 9 In Example 4 and Figure 5 Examples 9 and 10 and Comparative Examples 9 and 10 show the case where only the temperature of the nitriding treatment is changed compared with Example 4. Figure 5 Comparative Examples 3 to 6 show the case where only the temperature of the nitriding treatment was changed compared to Comparative Example 2 and the NH 3 flow rate was maintained at 5 liters / minute.

[0124] In the case where the heat treatment temperature of the nitriding treatment was 375°C and 450°C as shown in Examples 9 and 10, the FeNiN formation rates were 76% and 80%, respectively, but the ammonia efficiencies were 18.4 (×10 -5 ) and 19.2(×10 -5 ). In addition, the efficiency improvement rates were also high values ​​of 3.9 and 4.1, respectively. Moreover, even in the case where the temperature of the nitriding treatment was set to 415° C. (which was a temperature between Examples 9 and 10) as shown in Example 4, the ammonia efficiency and the efficiency improvement rate were high.

[0125] In addition, in the case where the heat treatment temperature of the nitriding treatment was 325° C. and 500° C. as shown in Comparative Examples 9 and 10, the FeNiN formation rates were 12% and 3%, respectively, and the ammonia efficiencies were 2.9 (×10 -5 ) and 0.72(×10 -5 ). The efficiency improvement rates were 0.61 and 0.15, respectively. From these results, it can be seen that in the case where 0.14 mass% of S is added, the ammonia efficiency and the efficiency improvement rate are improved by setting the temperature of the nitriding treatment in the temperature range of higher than 325°C and lower than 500°C. More preferably, it can be seen that the ammonia efficiency and the efficiency improvement rate can be improved by setting the nitriding temperature in the temperature range of 375 to 450°C.

[0126] On the other hand, in Comparative Examples 2 and 4, the FeNiN formation rate, ammonia efficiency and efficiency improvement rate are relatively high values, but in Comparative Examples 3, 5 and 6, the FeNiN formation rate, ammonia efficiency and efficiency improvement rate are relatively low or zero.

[0127] Specifically, in the case where the temperature of the nitriding treatment was 300° C. and 325° C. as in Comparative Examples 2 and 4, the FeNiN formation rates were 99% and 95%, respectively, and the ammonia efficiency was 4.7 (×10 -5 ) and 4.6(×10 -5 ). The efficiency improvement rates are 1 and 0.98 respectively.

[0128] When the temperature of the nitriding treatment was 275°C (which was lower than 300°C) as in Comparative Example 3, the FeNiN formation rate was 0%, the ammonia efficiency was 0, and the efficiency improvement rate was 0. Similarly, when the temperature of the nitriding treatment was 375°C and 415°C as in Comparative Examples 5 and 6, the FeNiN formation rates were 9% and 0%, respectively, and the ammonia efficiencies were 0.43 (×10 -5 ) and 0, and the efficiency improvement rate was low values ​​of 0.09 and 0, respectively. These results indicate that, in the case where no S is added, the desired ammonia efficiency and efficiency improvement rate cannot be obtained unless the temperature of the nitriding treatment is in the range of 300 to 325°C.

[0129] As described above, in the case where S is added therein, by setting the temperature of the nitriding treatment to at least a temperature range of 375 to 450°C, the desired ammonia efficiency and efficiency improvement rate can be obtained. On the other hand, in the case of a conventional manufacturing method in which S is not added, the desired ammonia efficiency and efficiency improvement rate cannot be obtained unless the temperature of the nitriding treatment is at least in the temperature range of 300 to 325°C. Therefore, by adding S, the temperature range in which the desired ammonia efficiency and efficiency improvement rate can be obtained can be expanded, and the process temperature can also be increased and the process window can be expanded. If the process temperature can be increased, FeNiN-S can be synthesized at a higher temperature, thereby increasing the crystallinity of the FeNi superlattice. Therefore, the characteristics of the FeNi superlattice can be improved. In addition, if the process window can be expanded, the temperature of the nitriding treatment can be set within the range of the process window, which is conducive to temperature control.

[0130] The above describes an example in which the sulfur content is 0.14 mass % as in Example 4, and based on the results of Examples 4, 9, and 10, the temperature of the nitriding treatment should be at least in the temperature range of 375 to 450° C. However, this is only one example, and for example, as shown in Example 1, by setting the temperature of the nitriding treatment to at least 335° C. or higher, a high ammonia efficiency and a high efficiency improvement rate can be obtained. Therefore, in the case in which the sulfur content is 0.03 mass % or more and 2.26 mass % or less, the temperature of the nitriding treatment can be set in the range of 335 to 450° C., so that the process window can be further expanded.

[0131] Furthermore, by changing the nitriding treatment time while maintaining the sulfur content, the FeNiN formation rate, ammonia efficiency, and efficiency improvement rate were studied. Specifically, in the case where the sulfur content was set to 0.05 (mass %) as in Example 3 above, the experiment was conducted by changing the nitriding treatment time. In addition, as a comparative example, a similar experiment was conducted on a conventional manufacturing method. Fig.10 is a graph showing the results. Fig.10 In Example 3 and Figure 5 Examples 12 and 13 show the case where only the nitriding treatment time is changed compared with Example 3. Figure 5 Comparative Examples 7 and 8 show the case where only the nitriding treatment time is changed compared with Comparative Example 2.

[0132] Even in the case where the time of the nitriding treatment was 10 hours and 20 hours (which were shorter than 40 hours) as shown in Examples 12 and 13, the FeNiN formation rates were 88% and 93%, respectively, and the ammonia efficiencies were 84.6 (×10 -5 ) and 44.9(×10 -5). In addition, the efficiency improvement rate is also high at 17.9 and 9.5, respectively. Therefore, it can be said that when S is added therein, even if the time of the nitriding treatment is shortened, the ammonia efficiency and the efficiency improvement rate can be improved.

[0133] On the other hand, in the case where the nitriding treatment time was 10 hours and 20 hours as in Comparative Examples 7 and 8, the FeNiN formation rates were 5% and 40%, respectively, and the ammonia efficiencies were 0.97 (×10 -5 ) and 3.9(×10 -5 ). The efficiency improvement rates were 0.20 and 0.82, respectively. These results show that, in the case where no S is added, the desired ammonia efficiency and efficiency improvement rate cannot be obtained unless the nitriding treatment time is 40 hours or longer.

[0134] As described above, in the case where S is added, even if the time of the nitriding treatment is shortened from 40 hours, a high ammonia efficiency and a high efficiency improvement rate can be obtained.

[0135] For reference, the order and magnetic properties of FeNi superlattice magnet powders obtained by denitrifying FeNiN of Comparative Example 2, Example 3 and Example 7 at 250°C for 4 hours were examined. The order of the FeNi superlattice obtained by denitrifying the FeNi nitride of Comparative Example 2 was 0.71, while the order of the FeNi superlattice obtained by denitriding the FeNi nitride of Example 3 was 0.68, which are almost the same. The order of Example 7 was 0.60. Fig.11 The respective hysteresis curves are shown. The coercive force of Comparative Example 2 is 142 kA / m. On the other hand, the coercive force of Example 3 is 135 kA / m, and the coercive force of Example 7 is 120 kA / m. The saturation magnetization of Comparative Example 2 is 139 Am 2 / kg, and the saturation magnetization intensity of Example 3 is also 139Am 2 / kg. The saturation magnetization of Example 7 is 91Am 2 / kg. From these results, it can be seen that the FeNi superlattice to which an appropriate amount of S is added as in Example 3 has the same performance as the FeNi superlattice to which S is not added as in Comparative Example 2. Since excessive sulfur causes a decrease in saturation magnetization as in Example 7, the sulfur content is preferably 2 mass % or less from the viewpoint of magnetic performance.

[0136] From these results and Figure 5From the measurement results of the XRD patterns of Comparative Example 2 and Example 3 shown in , it can be seen that no effect of doping with an appropriate amount of sulfur on the crystal structure and magnetic properties was observed. Therefore, it can be said that even if sulfur is doped, the ammonia efficiency during the manufacture of the FeNi superlattice can be improved without deteriorating the performance, and the production efficiency of the FeNi superlattice can be improved.

[0137] In addition, the inventors of the present invention examined the oxidation number of sulfur contained in the FeNi superlattice magnetic powders obtained in Examples 3 and 4. Specifically, XAFS measurement (ie, partial fluorescence yield measurement) was performed at Aichi Synchrotron Light Center BL6N1 according to the following procedure.

[0138] (1) Energy calibration

[0139] Before measuring the sample, SK-edge XANES measurement was performed on K2SO4 as a standard sample, and energy calibration was performed so that the peak top at that time was 2481.70 eV.

[0140] (2) Sample preparation

[0141] The sample was embedded in an indium sheet and attached to a sample holder using a conductive carbon tape. The sample holder with the sample attached was introduced into a He atmospheric pressure chamber and He replacement was performed for about 30 minutes before measurement.

[0142] (3) Main measurements

[0143] Partial fluorescence yield measurements were performed in the measurement range of 2440 to 2550 eV. The incident light had an incident angle of 20° relative to the sample plate.

[0144] (4) Analysis of measurement results

[0145] The inventors of the present invention analyzed the measurement results using "Athena" as the analysis software. Flattening and normalization were performed by setting the end E0 of 2471 eV, the pre-edge range of 2440 to 2470 eV, and the normalization range of 2508 to 2547 eV. Then, by comparing with the standard sample, it was determined whether there was any difference due to S 6+ The absorption peaks and the absorption peaks due to S 2- The presence of an absorption peak is determined by an increase in the absorption intensity by 10 times or more of the noise level (i.e., an S / N ratio of 10 or more). The noise level is the average of the absolute values ​​of the signal deviations in the range of 2440 to 2460 eV in the edge range. (NH4)2SO4 is used as S 6+Standard sample. FeS was used as S 2- Standard sample. The absorption peak at 2482.0±2eV is due to S 6+ The absorption peak at 2471.5±2eV is due to S 2- Based on the presence of these absorption peaks, it is determined that S 2- and S 6+ state.

[0146] As a result of the measurements and analysis, we obtained Fig.12 The results shown in . Fig.12 1 is a diagram showing the X-ray absorption near edge spectra (XANES) of the FeNi superlattice magnetic powders of Examples 3 and 4, respectively. Fig.12 Also shown are the X-ray absorption near-edge spectra of (NH4)2SO4 and FeS as standard samples. Fig.12 As shown in Examples 3 and 4, the oxidation number of sulfur is S 2- and S 6+ Compared with Example 4, Example 3 contains more S 6+ Compared with Example 3, Example 4 contains more S 2- Incidentally, although not shown, it was confirmed that the oxidation number of sulfur before and after the denitrification treatment was substantially the same in each of Examples 3 and 4.

[0147] from Fig.12 The results shown in show that the sulfur contained in the FeNi superlattice is not in the state of elemental sulfur, but in the state of combining with other elements. Fig.12 The results shown in Figure 5 The ammonia efficiency results of Examples 3 and 4 shown in FIG. 1 and FIG. 2 show that the effect of improving ammonia efficiency can be obtained even if the oxidation number of sulfur is different. In Examples 3 and 4, the oxidation number of sulfur is S 2- and S 6+ mixed state, but even if the oxidation number of sulfur is only S 2- and S 6+ In addition, the oxidation number of sulfur contained in the FeNi superlattice can be S 2- and S 6+ Any value other than may be used as long as the effect of improving ammonia efficiency can be obtained.

[0148] (Other implementation schemes)

[0149] Although the present disclosure has been described according to the above-mentioned embodiments, the present disclosure is not limited to these embodiments and includes various modifications and equivalent modifications. In addition, although various elements are shown in various combinations and configurations that are exemplary, other combinations and configurations including more, less or only a single element are also within the spirit and scope of the present disclosure.

[0150] For example, in the first embodiment, S is doped into FeNi oxide, and in the second embodiment, S is doped into FeNi alloy, but the doping of S can also be performed during the nitriding process. In the first embodiment, S can be doped at the Fe, Ni salt or FeNi alloy stage. S can be doped during the nitriding process. In addition, the doping method of S is not limited to the method described in the first and second embodiments, and any method can be used. For example, ammonium sulfate can be added to the raw material and then heat treatment can be performed, or H2S can be applied to the raw material. For example, FeNi-S can be synthesized by any method, such as by adding ammonium sulfate to metal FeNi or by mixing H2S with NH3 gas during nitriding for impregnation nitriding.

[0151] In the above-mentioned second embodiment, as an example of the case where S is segregated in the FeNi superlattice, S is segregated on the surface of the particles of the FeNi superlattice. However, S may be segregated to a portion other than the surface. For example, S may be segregated inside the particles of the FeNi superlattice.

[0152] The present disclosure is not limited to the above-mentioned embodiments and can be appropriately modified. In the above-mentioned embodiments, unless it is clearly stated that the element or feature is necessary, or unless the element or feature is obviously necessary in principle, the individual elements or features of the specific embodiments are not necessarily necessary. In addition, in the above-mentioned embodiments, when the numerical values ​​of the constituent elements of the embodiments are mentioned, such as number, quantity and range, etc., except when the numerical values ​​are clearly indispensable (especially, when the numerical values ​​are obviously limited to specific numbers in principle), the present disclosure is not limited to specific numbers.

[0153] Various aspects of the present disclosure will be described below. According to a first aspect, an L10-type FeNi ordered alloy has an L10-type ordered structure and contains sulfur.

[0154] According to a second aspect, the L10 type FeNi ordered alloy according to the first aspect has a sulfur content of 0.01 mass % or more.

[0155] According to a third aspect, the L10 type FeNi ordered alloy according to the first aspect or the second aspect has a sulfur content of 10 mass % or less.

[0156] According to a fourth aspect, the L10 type FeNi ordered alloy according to any one of the first to third aspects is composed of particles 100 having an L10 type ordered structure, and the sulfur exists throughout the particles.

[0157] According to a fifth aspect, the L10 type FeNi ordered alloy according to any one of the first to third aspects is composed of particles 100 having an L10 type ordered structure, and the sulfur is segregated to the particles.

[0158] According to a sixth aspect, in the L10 type FeNi ordered alloy according to the fifth aspect, the sulfur is segregated on the surface of the particles.

[0159] According to a seventh aspect, in the L10-type FeNi ordered alloy according to any one of the first to sixth aspects, the oxidation number of sulfur includes S 2- or S 6+ or S 2- and S 6+ of mixed state.

[0160] According to an eighth aspect, a method for producing an L10-type FeNi ordered alloy includes subjecting a FeNi alloy containing sulfur to a nitriding treatment to obtain a nitride containing Fe and Ni.

[0161] According to a ninth aspect, in the method for producing an L10 type FeNi ordered alloy according to claim 8, the sulfur content in the FeNi alloy is 0.01 mass % or more.

[0162] According to a tenth aspect, in the method for producing an L10 type FeNi ordered alloy according to the eighth aspect or the ninth aspect, the sulfur content in the FeNi alloy is 10 mass % or less.

[0163] According to an eleventh aspect, in the method for producing an L10-type FeNi ordered alloy according to any one of the eighth to tenth aspects, the nitriding treatment includes heat treatment at a temperature in the range of 300 to 500°C.

[0164] According to a twelfth aspect, in the method for producing an L10-type FeNi ordered alloy according to any one of the eighth to eleventh aspects, the nitriding treatment includes heat treatment at a temperature in the range of 330 to 450°C.

[0165] According to the thirteenth aspect, in the method for producing the L10-type FeNi ordered alloy according to any one of the eighth to twelfth aspects, the nitriding efficiency in the nitriding treatment for obtaining the nitride containing Fe and Ni is greater than 4.7×10 -5 .

Claims

1. FeNi nitride containing sulfur, wherein: The sulfur content is 0.01 mass % or more and 10 mass % or less.

2. The FeNi nitride according to claim 1, wherein: The sulfur content is 0.03 mass % or more and 2.26 mass % or less.

3. The FeNi nitride according to claim 1, wherein: The FeNi nitride is composed of particles, and the sulfur exists throughout the particles.

4. The FeNi nitride according to claim 1, wherein The FeNi nitride is composed of particles, and the sulfur is segregated inside the particles.

5. The FeNi nitride according to claim 1, wherein: The FeNi nitride is composed of particles, and the sulfur is segregated on the surfaces of the particles.

6. The FeNi nitride according to any one of claims 3 to 5, wherein: The particles have an average particle size of 10 nm or more and 5000 nm or less.

7. The FeNi nitride according to claim 1, wherein: The FeNi nitride is composed of secondary particles in which primary particles are aggregated, and an average particle diameter of the primary particles is 10 nm or more and 1000 nm or less.

8. The FeNi nitride according to claim 1, wherein: The FeNi nitride includes FeNiN, and a ratio of the FeNiN in the FeNi nitride is 50 mass % or more.

9. The FeNi nitride according to claim 8, wherein: The ratio of the FeNiN in the FeNi nitride is 80 mass % or more.

10. The FeNi nitride according to claim 1, wherein: In the FeNi nitride, the ratio of the mole number of Fe to the total mole number of Fe and Ni is 0.4 to 0.6.